Impact of brewery waste on the productive and reproductive indices in Jersey crossbred dairy cattle: Impact of brewery waste on productive and reproductive indices - Balakrishnan, Rajesh Kumar (Indian Journal of Dairy Science, 2024)
The study was conducted in twenty four Jersey crossbred dairy cows for a period of one year with three treatments to study the impact of brewery waste on productive and reproductive indices. The control group (T0) and brewery waste (T1) treatment was carried out in first farmer’s field and balanced ration (T2) treatment was carried out in second farmer’s field with eight animals in each group. The control, brewery and balanced ration animals were fed as per traditional and standard feeding practices. Productive indices viz., Milk yield, Milk fat, Solids Not fat (SNF), Body weight were assessed before and at the end of experiment. Reproductive indices viz., Lactation period, dry period and number of services per conception (SPC) were also assessed. The results of the study indicated that for T1, milk yield and body weight increased significantly (P<0.05) than control but lower than T2. Notable decrease of milk fat and SNF is evident for T1, which could affect the profit of dairy farmer. Among the reproductive indices, lactation period (299.99 days) were higher for T1 than control but lower than T2. With regard to dry period and SPC, brewery waste exhibited lower values (66.10 days and 2.00) than control but higher than T2. To conclude, complete feeding of brewery waste to lactating dairy animals should not be followed so as to avoid the decrease in milk fat and SNF content of milk which could affect profitable dairy farming.